Africa in Chaos - AYITTEY, George B N.; George B.N. Ayittey (New York: St. Martin's Griffin, 1999)
Summary: Explores the effect of colonial European government systems on Africa's economic and political situation at the end of the twentieth century.
Includes bibliographical references (pages 373-385) and index.
Adult
Keywords: South Africa